Lived Experience of Older Adults with Post-Hip Fracture - Bista Thapa, Bishnu (International Journal of Social Sciences and Management, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE NE <![endif]–> Objective: this phenomenological study was undertaken to explore lived experiences of community dweller older adults with post hip fractured. Methods: A qualitative research design underpinned by the philosophy of Edmund Husserl and methodological interpretations of Colaizzi’s. The series of in-depth web based interviews were simultaneously conducted and analyzed until saturation of data. Rigor of the study was maintained by validated the transcribed information by informants. Findings: based on subjective information provided by informants, sixteen themes were emerged which further merged into four theme clusters that were patho-dynamic of hip fracture, affected reaction to distress and situation appraisal, limitation in movement and being dependent on others and coping behaviors. Findings of this study indicated that informants experienced both fluid and complex that challenges all spheres of their life after hip fracture. Conclusion: It was concluded that, older adults with post-hip fracture are facing multiple situational problems like physical, emotional, care-givers and financial so that comprehensive, affordable and culturally based multi-disciplinary services are essential. Physical comforts, motivation, continuous support, encouragement for exercise, walking and financial assistance can promote their early recovery and regaining functional capacity. This approach to the study of lived experience of older adults with post-hip fracture offers an opportunity to reflect and make sense of their current situation in the light of their day to day life activities, struggling and achieving pre-fracture functional abilities, to tell their story to an interested listener and to have their feelings validated. DOI: http://dx.doi.org/10.3126/ijssm.v1i1.9590 Int. J. Soc. Sci. Manage. Vol.1(1) 2014 35-40 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:6.0pt; mso-para-margin-left:0cm; text-align:center; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-ansi-language:EN-US; mso-fareast-language:EN-US; –> <!–[endif] –>